THE MODERATING EFFECT OF PROFITABILITY ON DIVIDEND POLICY IN INDONESIAN INFRASTRUCTURE COMPANIES - Abdul Karim, Abdul Karim; Felina C Young, Felina C Young; Yuana Fasya Purnamasari, Yuana Fasya Purnamasari; Hendra Galuh Febrianto, Hendra Galuh Febrianto; Dhea Zatira, Dhea Zatira; Amalia Indah Fitriana, Amalia Indah Fitriana (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Research on the dividend policy of infrastructure companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023 is important, as this sector plays a vital role in economic growth. Infrastructure companies require substantial capital for long-term projects, so their dividend policies reflect a priority on profit allocation, both for reinvestment and distribution to shareholders. The study aims at providing insights into the factors influencing dividend policy in the sector. Using quantitative methods with panel data regression and moderation analysis, the authors analyzed 63 purposively sampled companies. The results showed that solvency and growth had no partial effect on dividend policy, whereas liquidity did. However, when tested simultaneously, three variables solvency, growth, and liquidity significantly affected dividend policy. Profitability only moderates the company's growth influence. These findings serve as a guide for policymakers and close the gap in previous research on the role of profitability as a moderation variable.